Improving the quality of weekend handover at Yeovil District Hospital. Issue 1 (2nd September 2014) - Sneller, Sarah; Lada, Karolina; Turner, Charlotte; Millwood, Sinead; Jervis, Bethan; Barr, Julia; Farrell, Louise
Abstract: "Handover of care is one of the most perilous procedures in medicine" (British Medical Association, Safe Handover, Safe Patients). The system in place for weekend handover at YDH was deemed disorganised, unstructured and frequently missing key pieces of information, leaving the on-call Foundation Year 1 (FY1) doctor with only vague jobs and management plans. Baseline surveys demonstrated that junior doctors felt the system was inadequate, potentially compromised patient safety and increased their stress levels. In order to improve this problem a structured weekend handover proforma was created, comparable with the "Out of hours handover record keeping standards: template" from the Royal College of Physicians. This was made readily accessible on the local intranet. Education sessions were organised for the FY1 and FY2 doctors. The impact of the newly introduced proforma was measured using feedback surveys each week from the FY1 on ward cover for six months. A further change implemented was the introduction of a Friday Ward Round proforma. The aim was to reduce the time required to review notes by the on-call doctor, to minimise avoidable weekend jobs and to improve compliance with the management plans. The results demonstrated 100% compliance with the new proformas. There were notable improvements in the presence of a plan (37.5% to 91.7%, max. 100%), a minimum of two patient identifiers (68.8% to 100%) and relevant background information (62.5% to 100%). Qualitative data showed a much higher level of satisfaction with the new system. Future plans include rolling out electronic handover to improve problems such as illegible handwriting and missing data (enable 'compulsory' fields), and also for this system to be implemented Trust-wide.